Sensitivity of Populus deltoides Young Aged Stem Cuttings (Six Months) to Gamma Rays and its Synergistic Effects with Kinetin - Chauhan, P.S.; Singh, S.S. (Indian Journal of Agroforestry, 2020)
Stem cuttings of P deltoides have been irradiated with different continuous and fractionated doses of gamma rays (500R, 1 KR, 2 KR, 4 KR) to observe the regeneration sensitivity. Irradiated cuttings have got early sprouting than control. At 1 KR-C dose level maximum sprouting (50%) have been recorded and it was minimum at 1 KR-F treatment in comparison to control after 29 days of potting. The lateral shoot growth was favored by continuous doses. Maximum shoot length (2.8 cm) has been recorded under 1 KR-C treatment. Leaf numbers per cutting have also been augmented by the gamma rays treatments. The maximum numbers of leaves per cutting (11.0 ± 2.58) have been recorded at 4 KR-F treatment followed by 500 R-C treatment (9.1 ± 2.98). Maximum area of the leaf (805.6 ± 7.95 cm2) has been observed at 4 KR-F level. The mortality percentage of the sprouted buds influenced by different continuous and fractionated doses of gamma rays. The maximum mortality percentage of the sprouted buds have been recorded at 500R-C (88.2 %) and minimum at 500 R-F + Kinetin 500 ppm combination (0%) treatments after 44 days of potting. The gamma rays break the bud dormancy in the clones at different levels and augmented the sprouting percentage and its subsequent growth. Kinetin combinations showed antagonistic effects in irradiated stem cuttings of P. deltoides. But sprouting is delayed and sprouting percentage has been reduced in combination treatment. Leaf area has also been reduced drastically in irradiated cuttings with Kinetin 500 ppm combination. The lateral branch growth has increased under Kinetin combinations. Mortality percentage of the buds has been reduced by Kinetin 500 ppm treatment to gamma rays treated stem cuttings.